2012
DOI: 10.1245/s10434-012-2271-0
|View full text |Cite
|
Sign up to set email alerts
|

A 5 Year Analysis of Readmissions after Radical Subtotal Gastrectomy for Early Gastric Cancer

Abstract: Readmission rate at 1 month after radical subtotal gastrectomy is lower than that after major bowel surgery. Unusual postoperative recovery in a patient with vague symptoms should be managed with greater care before discharge. After subtotal gastrectomy for early gastric cancer, prevention of readmission can improve the patient's quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 19 publications
5
20
1
Order By: Relevance
“…In this study 12.2% of patients required readmission, which is comparable to published data (7, 10, 14, 15). If included in the model for mortality, NSQIP defined readmission is associated with lower risk of mortality.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study 12.2% of patients required readmission, which is comparable to published data (7, 10, 14, 15). If included in the model for mortality, NSQIP defined readmission is associated with lower risk of mortality.…”
Section: Discussionsupporting
confidence: 90%
“…Institutional and registry data suggest an overall morbidity of approximately 20% and increased risk of readmissions among patients who developed complications (7, 10, 14, 15). The individual effects associated with specific and potentially modifiable risk factors remain poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…Although our results were not directly comparable to those of Wang et al [16], those authors reported that readmission rates in ERAS and non-ERAS were 2.22 and 2.12%, and the main causes of readmission in ERAS and non-ERAS were gastric stasis and bowel obstruction, respectively. In this study, the most common readmission cause both within and after 30 days was bowel obstruction, and these results were comparable with other reports [26,27]. …”
Section: Discussionsupporting
confidence: 93%
“…Gastric cancer is one of the most common digestive tract malignancies worldwide, and surgical resection is the only therapeutic modality for cure 1. The resection method includes total gastrectomy (TG) and subtotal gastrectomy (SG).…”
Section: Introductionmentioning
confidence: 99%